Facies and architectural analysis of Paleogen fluvial deposits of the measured section of Rambangnia and Air Napalan Rivers in Palembang Sub-basin - Daryono, Sapto Kis; Prasetyadi, Carolus; Paripurno, Eko Teguh; Sutanto, Sutanto; Faozi, Aditya Zaenalfi (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2022)
Paleogene fluvial deposits have an important problem as pre-rift deposits, which occur before or at the same time as the formation of the basin. The research results on facies analysis and interpretation of the depositional environment of Paleogene deposits located in the Garba Hills will later explain and describe the history of the formation and stratigraphic evolution of sedimentary rocks in the South Sumatra Basin, reflected in the lithological and facies characteristics. The facies analysis was carried out on a stratigraphic cross-section with a thickness of ± 107.37 meters and ± 11.06 meters on the measurement path of the Rambangnia River and Air Napalan River, which are located in the Ogan Komering Ulu area, South Sumatra. Seven lithofacies developed on two measured paths are matrix supported gradded gravel (Gmg), gravel matrix supported Massive (Gmm), through cross-bedded (St), massive sandstone (Sm), horizontally bedded sandstones (Sh), parallel laminated siltstone and claystone (F1), massive siltstones and mudstones (Fsm). Asosiasi fasies didapatkan berupa Sedimentary Gravity Flow (SG), Gravel Bars (GB), Sandy Bedforms (SB), channel (CH), Overbank fine (FF). The interpretation of the depositional environment shows a fluvial environment, the type of braided river with a gravel braided rivers model with sedimentary gravity flows.Paleogene fluvial deposits have an important problem as pre-rift deposits, which occur before or at the same time as the formation of the basin. The research results on facies analysis and interpretation of the depositional environment of Paleogene deposits located in the Garba Hills will later explain and describe the history of the formation and stratigraphic evolution of sedimentary rocks in the South Sumatra Basin, reflected in the lithological and facies characteristics. The facies analysis was carried out on a stratigraphic cross-section with a thickness of ± 107.37 meters and ± 11.06 meters on the measurement path of the Rambangnia River and Air Napalan River, which are located in the Ogan Komering Ulu area, South Sumatra. Seven lithofacies developed on two measured paths are matrix supported gradded gravel (Gmg), gravel matrix supported Massive (Gmm), through cross-bedded (St), massive sandstone (Sm), horizontally bedded sandstones (Sh), parallel laminated siltstone and claystone (F1), massive siltstones and mudstones (Fsm). Asosiasi fasies didapatkan berupa Sedimentary Gravity Flow (SG), Gravel Bars (GB), Sandy Bedforms (SB), channel (CH), Overbank fine (FF). The interpretation of the depositional environment shows a fluvial environment, the type of braided river with a gravel braided rivers model with sedimentary gravity flows.